Correlation of Gestational Age by Last Menstrual Period, Ultrasonography and New Ballard’s scoring - Dr Indra N; Dr Pradeep NM; Dr Hema KR; Dr Prerana M Ganaboor, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Gestational age or menstrual age is the time elapsed from the first day of last menstrual period (LMP), a time that precedes conception. The accurate calculation of gestational age holds key role in prevention of preterm birth; hence the study attempts to find which method gestational age calculation is more accurate. Methods: prospective observational study with 179 participants whose gestational age was assessed using last menstrual period (LMP), ultrasonography (USG) and New Ballard scoring (NBS) which is considered gold standard. Results: The mean age of the mother in our study is 24.68 years with a standard deviation of 3.99 and the mean birth weight of babies in our study is 2.80 kg with a standard deviation of 0.45. Pearson coefficient correlation is 0.677 (P <0.001) when comparing gestational age by LMP and gestational age by NBS which is statistically significant. A correlation of 0.779 (P <0.001) was found while comparing gestational age by T1 USG and NBS which was also found to be significant. Conclusion: T1 USG is more consistent with NBS when compared to LMP gestational age, even though both have positive correlation with NBS.